Yorkie and Scalloped signaling regulates Notch dependent lineage specification during Drosophila hematopoiesis - Ferguson, Gabriel B. (Curr Biol, 2014)
Cellular microenvironments established by the spatial and temporal expression of specific signaling molecules are critical for both the maintenance and lineage-specific differentiation of progenitor cells. In Drosophila, a population of hematopoietic progenitors, or prohemocytes, within the larval lymph gland [1] gives rise to three mature cell types: plasmatocytes, lamellocytes, and crystal cells. Removal of the secreted signaling molecules Hedgehog [2] and PVF1 [3] from the Posterior Signaling Center (PSC)[2, 4, 5] which acts as a niche, leads to a loss of progenitors and complete differentiation of the lymph gland. Here, we characterize a novel population of signaling cells within the lymph gland, distinct from the PSC, that are required for lineage specific differentiation of crystal cells. We provide evidence that Yorkie[6] and Scalloped[7], the Drosophila homologues of YAP and TEAD, are required in Lineage Specifying Cells to regulate expression of Serrate, the Notch ligand responsible for the initiation of the crystal cell differentiation program[8] [5]. Genetic manipulation of yorkie and scalloped in the lymph gland specifically alters Serrate expression and crystal cell differentiation. Furthermore, Serrate expression in Lineage Specifying Cells is eliminated in the Lymph Gland upon the immune response induced by wasp parasitization to ensure the proper differentiation of lamellocytes at the expense of crystal cells. These findings expand the roles for Yorkie/Scalloped beyond growth to encompass specific cell fate determination in the context of blood development. Similar regulatory functions may extend to their homologues in vertebrate progenitor cell niches that are required for specifying cell fate.